ANALISIS PENERAPAN STANDARD OPERATING PROCEDURE OLEH TELEPHONE OPERATOR DAN IMPLIKASINYA TERHADAP PENINGKATAN PELAYANAN DI HOLIDAY INN RESORT BARUNA BALI (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This study aims to analyze the implementation of Standard Operating Procedure (SOP) by telephone operators and its implications for service improvement at Holiday Inn Resort Baruna Bali. The background of this research is based on changes in work structure due to employee reductions during the pandemic, which caused telephone operators to take over some of the duties of the Guest Relation Officer (GRO). This research uses a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. The results showed that the SOPs implemented have provided clear work guidelines and helped telephone operators carry out their duties professionally despite facing a double workload. However, obstacles such as fatigue, division of focus, and lack of SOP updates are still felt by the staff. Management has responded to these constraints by providing training, supervision, and additional support through the recruitment of daily workers. Effective implementation of SOPs has proven to have a positive impact on service quality and guest satisfaction, but periodic evaluation and adjustment of SOPs are still needed to make them more adaptive to operational dynamics.